Implementation of Smart Board Multiplication Learning Media in Mathematics Learning for Grade III at UPTD SDI Malamude - Mau Gili, Angela Marici; Ngura, Elisabeth Tantiana; Natal, Yanuarius Ricardus; Meka, Marsianus (CV. Tripe Konsultan, 2025)
Children’s learning outcomes can be enhanced through the use of appropriate media that stimulate thinking skills, motivation, and engagement. At UPTD SDI Malamude, many third-grade students were observed to struggle with mathematics, particularly in multiplication. This study aimed to examine the effectiveness of smartboards as a learning medium to improve students’ understanding of multiplication. The research applied a qualitative method with a descriptive approach. Data were gathered through observation, interviews, and documentation, involving third-grade students at UPTD SDI Malamude. The analysis used descriptive qualitative techniques to interpret and explain the findings. Results indicate that smartboards significantly contributed to improving student motivation and mastery of multiplication. Of the 19 students involved, 16 (84%) successfully achieved learning mastery, while 3 students (16%) still experienced difficulties. The integration of smartboards provided an interactive and enjoyable classroom atmosphere, making mathematical concepts easier to comprehend and more engaging for students. The study concludes that smartboards are an effective instructional medium for teaching multiplication. Their use not only enhances students’ numeracy skills but also helps teachers create dynamic, fun, and student-centered learning environments. Therefore, the application of smartboard-based learning in mathematics can serve as a valuable strategy to improve both student understanding and overall learning outcomes.